An endophytic strain JK of genus bacillus isolated from the seeds of super hybrid rice (Oryza sativa L., Shenliangyou 5814) has antagonistic activity against rice blast pathogen. (October 2020) - Jing, Ruixue; Li, Ni; Wang, Weiping; Liu, Yang
Abstract: Rice is an important food crop in the world, and rice blast is one of the major fungal diseases that cause large-scale rice yield reduction. This study aimed to investigate the antagonistic activity and its molecular mechanism of bacterial strain JK isolated from seeds of super hybrid rice 'Shenliangyou 5814' ( Oryza sativa L.) against rice blast pathogen Magnaporthe oryzae ACCC 36020. Through plate confrontation experiment, strain JK showed obvious and highly effective antagonistic activity against M. oryzae . And strain JK was identified as Bacillus velezensis by molecular biological identification basing on 16S rRNA gene and gyrA gene phylogenetic analysis. The draft genome of strain JK was sequenced by Illumina NextSeq500, and 1 CDS for beta-1, 4-glucanase (cellulase), 1 CDS for endo-beta-1, 3-1, 4 glucanase (licheninase), 2 CDS for 3-hydroxybutyrate dehydrogenase, 4 CDS for surfactin synthase, 28 CDS for polyketide biosynthesis were annotated and correlated to antagonistic activity. The present study provides a theoretical basis and microbial strain resources for further study on the biological control of rice blast. Highlights: Through plate confrontation experiment, strain JK showed obvious and highly effective antagonistic activity against Magnaporthe oryzae. Strain JK was identified as Bacillus velezensis. The genome of strain JK was sequenced and CDS for glucanase, 3-hydroxybutyrate dehydrogenase and surfactin synthase were annotated and correlated to antagonistic activity.